Proses Pembayaran Labuh Tambat Dan Pandu Pada Sistem BSIMS (Batam Seaport Information Management System) Pada PT. Pelayaran Nusabhakti Tatasegara Batam - Franciska Veronika Sinaga; Dina Rispianti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This paper explains the payment process for mooring and pilotage of PT. Pelayaran Nusabhakti Tatasegara Batam. The method used in this observation is field research. The author of the paper with library research activities where the author gets material or paper materials from books in the library or other reading sources related to the subject matter taken from PT. Pelayaran Nusabhakti Tatasegara is one of the companies engaged in the agency sector. PT. Pelayaran Nusabhakti Tatasegara Batam serves many types of ships ranging from tugboats-barges to LCT (Landing Craft Tank) cargo ships at Batam port. In its payment system using the BSIMS system after the PUK (General Statement of the ship) is issued at Bsim, it can be continued by carrying out the Fund hold process until it is paid off. The purpose of this paper research is to find out how the Payment Process for Mooring and Pilotage in the BSIMS Special Batam system by PT. Pelayaran Nusabhakti Tatasegara Batam. The process starts from registration to Paid Off. The conclusion of this paper is the payment process for Anchorage and Pilotage on the Special BSIMS System for Batam by PT. Pelayaran Nusabhakti Tatasegara Batam runs smoothly and in accordance with existing procedures, but there are still various obstacles experienced including network disruptions in the system which cause difficulties in inputting data into the system, double holds occur in the officer system, PUK does not come out because the PUK activity at the previous port has not been closed, which causes the PUK not to come out.